Why are catches in mixed fisheries well below TAC?. (July 2020) - McQuaw, Kristin; Hilborn, Ray
Abstract: In major mixed stock fisheries of the United States, the actual catch is well below the total allowable catch (TAC). In recent years, only 20–30% of the TAC is caught in the US West Coast non-whiting fishery, whereas 60–80% of the TAC is caught in the Gulf of Alaska groundfish trawl fishery. Possible explanations for the underutilization are (1) lack of infrastructure, (2) lack of market demand, and (3) low quota limits on some species restricting the ability to harvest other species. Using species by species data on catch, TAC and lease price for species under Individual Transferable Quotas, we evaluate the support for these hypotheses. The results suggest that rebuilding plans, under a strict timeline, ultimately created many of the choke species on the West Coast and reduced processing infrastructure, such that the fishery still struggles with low quota utilization even after stocks have been rebuilt. In comparison, the Gulf of Alaska has not had a history of rebuilding plans and generally has higher utilization. The results suggest that rebuilding plans intended to increase sustainable harvest have been successful at increasing abundance but have been unsuccessful at rebuilding the fishery. Highlights: In 2017 US mixed stock fisheries landed 30–60% of their TAC. In fisheries with mandatory rebuilding, only 20–30% of the TAC is caught. Dramatic cuts in TAC by rebuilding left the US West Coast limited by choke species and lost markets. Gulf of Alaska groundfish has no history of rebuilding plans and higher utilization. Mandatory timelines for rebuilding plans do not appear to be the best way to sustain fisheries.